Screening of novel conopeptide for mosquitocidal activity against lethal mosquitoes (Anopheles stephensi, Aedes aegypti) - Nguyen, Bao; Phan Thi, Khanh Vinh; Nguyen , Van Suu; LE CAER, Jean-Pière (Academia Journal of Biology, 2024)
Mosquitoes are carriers of various diseases that result in millions of human deaths annually. However, the use of chemical mosquitocides has led to significant concerns, such as adverse effects on the environment, human health, and insecticide resistance. As a result, there is a pressing need for eco-friendly alternatives. This study aimed to identify potential mosquitocidal conopeptides from cone snail venoms targeting two lethal mosquito species, Anopheles stephensi and Aedes aegypti. Eleven Conus species were collected from Nha Trang Bay and their crude venoms were dissected and collected. Through cell survival and toxicity assays on mosquito larvae, five crude venoms were identified to have inhibitory effects. Further investigations involved fractionating these five crude venoms and testing them for cell cytotoxic activity were conducted. Four fractions from Conus bandanus venom, named CB37, CB39, CB41, and CB43, showed significant cytotoxic activity against cell survival. Other fractions from different Conus venoms also exhibited some cytotoxic activity at high concentrations but were not prioritised for further investigation. Toxicity experiments on adult mosquitoes revealed that the CB41 fraction had the most potential, with an IC50 of 30 μM. Additionally, this CB41 compound is a peptide in nature and was found to have a native mass of 3332.1 Da and three disulphide bridges. These results could deduce this long-chain peptide possessing a compact structure. To our knowledge, the conopeptide CB41 is reported first time to have mosquitocidal activity.